2013
DOI: 10.1021/ef400275h
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Single-Phase and Two-Phase Water-in-Crude-Oil Dispersed Flow Wax Deposition in a Mini Pilot-Scale Flow Loop

Abstract: Wax deposition tests under single-phase and two-phase dispersed water-in-oil at 16 and 35% water cut (WC) were conducted in a mini pilot-scale flow loop by using South Pelto crude oil. The initial inner wall temperature (T̅ w,ini ) and the bulk fluid temperature (T b ) were controlled to be 85−87 °F and 105−107 °F, respectively, throughout the experimental program. The initial Reynolds number (Re ini ) of tests conducted in rectangular (TS1) and circular (TS2) test sections was in the range of 400−4300 and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 22 publications
11
84
0
1
Order By: Relevance
“…Figure 7 also shows that the water content of several deposit samples was close to 0 vol %, which confirms the observations by Kasumu and Mehrotra 22 and Panacharoensawad and Sarica. 29 That is, the water content of the deposit may not be related to the deposition process; instead, it might represent "wetness" of the deposit surface or physical attachment of water droplets to the deposit surface and/or entrapment or occlusion of water droplets within the deposit. This observation suggests the importance of measuring the water content of the deposit and expressing the deposit mass on a water-free basis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Figure 7 also shows that the water content of several deposit samples was close to 0 vol %, which confirms the observations by Kasumu and Mehrotra 22 and Panacharoensawad and Sarica. 29 That is, the water content of the deposit may not be related to the deposition process; instead, it might represent "wetness" of the deposit surface or physical attachment of water droplets to the deposit surface and/or entrapment or occlusion of water droplets within the deposit. This observation suggests the importance of measuring the water content of the deposit and expressing the deposit mass on a water-free basis.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[150] The presence of water in two-phase flows, as either water-in-oil or oil-in-water blend, has been reported to have inconclusive effects on wax deposition. While many studies have reported a decrease in wax deposition with increasing water fraction, [115,[150][151][152][153][154][155] others have reported an increase in wax deposition with increasing water fraction, [156,157] or no significant change due to the presence of water. [55,105] Clearly, more studies are needed to establish a conclusive effect of the presence of water on wax deposition.…”
Section: Water Droplets and Emulsionmentioning
confidence: 99%
“…The mass‐based technique requires pigging the wax deposit and residual oil after each test using a pig (Figure ). Equations and were used to calculate the wax deposit thickness assuming uniform wax deposit . It should be noted that for this method, the test must be stopped at each time point to collect the deposit from the test section.…”
Section: Experimental Programmentioning
confidence: 99%